Some variables affecting the Attitudes of University students attitudes towards the Political Participation of Women in Four Arab Societies - Alothman, Husein Mohammad; Medani, Khalil; Touhami, Brahim (Al-Adab Journal, 2020)
This study aims to identify attitudes of university students towards the dimensions of women’s political participation in four Arab societies. It also aims to examine the impact of some socio-demographic and economic variables on those attitudes. To achieve the aims of the study and answer research questions, a sample of university youth was randomly selected in four Arab universities (UAE, Jordan, Sudan and Algeria) to fill out a questionnaire; a total of 1773 questionnaires were completed. Descriptive statistics (percentages, means, and standard deviations) and analytical statistics (multiple linear regression) were applied in the analysis of the study data. Descriptive analysis of the data has revealed positive attitudes of university youth towards the political participation of women in Arab societies. However, these results differ in relation to the specific dimensions of political participation: Arab university youth hold more liberal attitudes towards women’s participation in civil society compared to their participation in the political process and their political status. Meanwhile, results of the inferential statistical analysis have shown that certain variables, namely country, gender, age, college, mother’s educational level, and religiosity have statistically significant relationships with all or some dimensions of political participation of Arab women.